Behavior of a new laterally top-loaded post-grouted micropile in highly porous lateritic soil - Yuri Barbosa; Murilo Heryaldo Pinheiro Tarozzo; Paulo José Rocha de Albuquerque; David de Carvalho (Dyna, 2023)
The use of micropiles has been increasing in recent years, mostly for horizontally loaded cases. Given the little information about this foundation type under lateral top-loading, especially in high-porosity and collapsible soils, a total of four transversal loading tests were carried out in a new post-grouted micropile configuration with length of 17 m and diameter of 0.3 m, two in natural soil moisture conditions and two in flooded conditions. Load-displacement curves and the horizontal reaction coefficient of the new micropile were obtained. Results were compared with other pile types laterally tested under the same conditions and in the same geological and geotechnical contexts. Generally, results were better than the other pile types, mainly under saturated condition. The new micropile proved to be a better and more efficient alternative for local lateritic soil treatment when compared with the soil-cement treatment.